LEVEL OF KNOWLEDGE OF PREGNANT WOMEN ABOUT CONSUMPTION OF FE TABLETS WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN: A CROSS SECTIONAL STUDY - Heriani; Ramayani (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Anemia among pregnant women remains a health challenge that can increase the likelihood of complications during pregnancy and childbirth. One important element in anemia prevention efforts is the extent of pregnant women's knowledge regarding the use of Fe tablets. With a good understanding, it is hoped that their level of compliance in consuming Fe tablets can increase, thereby reducing the incidence of anemia. This study aims to explore the relationship between pregnant women's knowledge regarding the use of Fe tablets and the frequency of anemia among pregnant women in the TPMB Bdn. Roslina, S. Keb, Ogan Komering Ulu Regency in 2025. The method used in this study is an analytical design with a cross-sectional approach. A sample of 42 pregnant women was taken using an accidental sampling technique. The measuring instruments used in the study were a questionnaire about pregnant women's knowledge regarding the consumption of Fe tablets and a hemoglobin level check sheet. To analyze the data, the Chi-Square test was used. The research findings revealed a significant relationship between pregnant women's knowledge regarding the consumption of Fe tablets and the incidence of anemia, with a p value = 0.044 (p < 0.05). From the results of this study, it can be concluded that there is a relationship between pregnant women's knowledge regarding Fe tablets and the incidence of anemia. It is hoped that medical personnel can increase education for pregnant women about the importance of taking Fe tablets consistently and correctly as a step to prevent anemia during pregnancy.